Synthesis of Some Novel Thiobarbituric Acid Derivatives and Their Related Compounds from Sulfa-Drug as Antiinflammatory - Aldin M. Zayed, Mohie (Asian Journal of Chemistry, 2014)
In search for new antiinflammatory agents, some new substituted thiobarbituric acids (2) and their bis-fused or fused thiopyrimidinyl-pyrimidinone (7, 8) have been derived from sulfathiazole and dimethylmalonate with CS2. structures of the synthesized compounds were established by spectroscopic (FT-IR, 1H NMR, 13C NMR, Mass) and elemental analyses. The antiinflammatory activity of these compounds was tested against carrageen-induced oedema with the reference of standard drug phenyl butazone. The results showed that compounds 2 and 3 are better antiinflammatory agents as compared to standard drug phenyl butazone.